(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Kidney dysfunction associated with hypothyroidism has become an increasingly recognized clinical entity in modern endocrinology and nephrology. Thyroid hormones play a fundamental role in maintaining renal hemodynamics, glomerular filtration, tubular transport processes, electrolyte balance, and cardiovascular stability. Deficiency of thyroid hormones may result in reduced renal blood flow, decreased glomerular filtration rate, elevated serum creatinine levels, sodium retention, and progressive impairment of renal function. Importantly, many of these abnormalities are potentially reversible following adequate thyroid hormone replacement therapy. Despite growing evidence supporting the association between hypothyroidism and renal dysfunction, diagnostic delays and underrecognition remain common in routine clinical practice.